2003
DOI: 10.1002/cne.10916
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in the inner ear: Comparison of distribution patterns in different vertebrates and assessement of connexin composition in mammals

Abstract: The distribution and size of gap junctions (GJ) in the sensory epithelia of the inner ear have been examined in a reptile (gecko), birds (chicken and owl), and mammals (mouse, guinea pig, gerbil, and bat), and the connexin composition of GJs in the mammalian inner ear has been assessed. Freeze fracture revealed a common pattern of GJ distribution in auditory and vestibular sensory epithelia in the different vertebrate classes. In all these tissues, GJs are numerous, often occupying more than 25% of the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
283
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 247 publications
(308 citation statements)
references
References 73 publications
(112 reference statements)
18
283
0
4
Order By: Relevance
“…cx31 immunofluorescence was restricted to apparently cytoplasmic sites, with few if any gap junction plaques being detected. cx31 has been described previously in type II fibrocytes (Xia et al 2000;Forge et al 2003), an observation we confirmed in guinea pig sections (data not shown). We also observed intracellular cx31 immunofluorescence in type III fibrocytes but not within intercellular plaque-like arrangements.…”
Section: Contractility In Type III Fibrocytes Is Modulated By Gap Junsupporting
confidence: 90%
“…cx31 immunofluorescence was restricted to apparently cytoplasmic sites, with few if any gap junction plaques being detected. cx31 has been described previously in type II fibrocytes (Xia et al 2000;Forge et al 2003), an observation we confirmed in guinea pig sections (data not shown). We also observed intracellular cx31 immunofluorescence in type III fibrocytes but not within intercellular plaque-like arrangements.…”
Section: Contractility In Type III Fibrocytes Is Modulated By Gap Junsupporting
confidence: 90%
“…Similar findings have been reported for both connexin 26 and connexin 30 (Ahmad et al 2003;Forge et al 2003). Sparse staining for connexin 26 for cells in this region was also noted in the initial report on its localization in rat (Kikuchi et al 1995).…”
Section: Cytochemistry Of Type IV Fibrocytessupporting
confidence: 85%
“…These observations are not compelling, however, because tissue preservation was not optimal due to the tissue processing protocol having been optimized for immunostaining sensitivity. Nevertheless, the assumption that all three noise bands used in the present study may have damaged the lower basal turn organ of Corti seems reasonable, based upon considerations of basilar membrane mechanics discussed above and upon previous reports of hair cell loss near the hook in a number of species following noise exposures with a variety of noise types (Fried et al 1976;Johnsson and Hawkins 1976;Liberman and Kiang 1978;Moody et al 1978;Salvi et al 1982;Wang et al 2002;Harding et al 2005).…”
Section: Adams: Type IV Fibrocytes 377mentioning
confidence: 53%
“…This maintenance ensures the longevity of sensory hair cells and the generation of the endocochlear potential. The ion transporting mechanisms that regulate these concentrations have been characterized in a number of cochlear tissues, leading to widely held hypotheses of K + "recirculation" and "spatial buffering" (Forge et al 2003a;Hibino and Kurachi 2006;Kikuchi et al 2000;Kikuchi et al 1995;Nickel and Forge 2008;Nin et al 2008;Spicer and Schulte 1996;Takeuchi et al 2000;Wangemann 2006;Weber et al 2001;. In common with these mechanisms studied in the CNS and retina (Kofuji and Newman 2004), cochlear K + recirculation and spatial buffering both rely on gap junctional coupling throughout the epithelial cell network, and the ability of cells at the edges of the network to secrete K + .…”
Section: Discussionmentioning
confidence: 99%
“…The supporting cells in the organ of Corti, together with the adjacent epithelial cells spanning the radial distance to the lateral wall, collectively form a syncytium known as the "epithelial gap junction network" (Kikuchi et al 2000). Gap junctions in the syncytium are formed from connexin26 (Cx26) and/or Cx30 subunits (Forge et al 2003a;Forge et al 2003b;Zhao and Yu 2006). Mutations in the Cx26 and Cx30 genes are a common cause of autosomal recessive non-syndromic deafness in humans (Nickel and Forge 2008).…”
Section: Root Cells Form the Lateral Limits Of The Epithelial Gap Junmentioning
confidence: 99%